Post-conflict disarmament, demobilization and reintegration bringing state-building back in - Giustozzi, Antonio (Global security in a changing world, 2012)
Revisits post-Cold War Disarmament Disintegration and Reintegration (DDR) programmes in the light of previous experiences of disarmament, demobilisation and reintegration. This book is suitable for policy makers, students and scholars of conflict studies, and those working in NGOs, particularly donor agencies.